Visualizing reactive oxygen species inside cancer cells after stimulation with polycyclic aromatic hydrocarbon via spontaneous formation of Au nanoclusters - Pilapong,C. (Elsevier, 2015)
© 2014 Elsevier B.V. All rights reserved. This research was designed to visualize cellular response - in particular the generation of intracellular ROS - to stimulation by polycyclic aromatic hydrocarbon (PAH). We used chloroauric acid (HAuCl4) as a molecular probe for visualizing intracellular ROS generated by the stimulation of benzo[a]pyrene (BaP). The chloroauric acid undergoes a spontaneous reduction reaction, assisted by the intracellular ROS, into gold nanoclusters (AuNCs). As a result, we can visualize the ROS via optical imaging technique. According to MTT assay, the chloroauric acid exhibited good biocompatibility. The AuNCs produced in the cells were approximately 2-3 nm in diameter with a green fluorescent property. Cellular imaging showed that BaP induced the formation of AuNCs within the cells, leading to a high relative cellular fluorescent intensity with a considerable extent of scatter light. Thus, this probe is an efficient molecular imaging probe for visualizing intracellular ROS.